Challenges and prospects of managing infectious diseases among pastoral and migrant populations - Prof Abdulrazaq Habib (International Journal of Infectious Diseases)
The detection, management and prevention of Infectious Diseases (IDs) in special contexts and situations may pose challenges. We present case studies of the circumstances among pastoralists, internally displaced populations (IDP) and migrant populations in sub-Saharan Africa that nurture IDs. Given the interplay of factors such as migratory lifestyle, livelihood, geographic inaccessibility, communication barriers, illiteracy and poverty, it is challenging for pastoralists, migrants and IDPs to access adequate care. Furthermore, the livelihoods of pastoralists often revolve around possession of livestock constantly mobile in search of water and pasturage which predisposes to zoonotic infections in addition to cosmopolitan infections. There are also inherent challenges in managing chronic infections as they are not settled and regular periodic follow-up may be extremely challenging. IDPs, especially children, become vulnerable to hunger and malnutrition, which, aided by poor immunization and the weakened healthcare system, makes the displaced persons susceptible to IDs such as measles, Noma, e.t.c. Overcrowding in IDP camps spawn respiratory and water-borne infections such as gastroenteritis, cholera, enteric fever as well as diseases of intimate contact such as scabies. Among pastoralists priority zoonotic diseases include bovine tuberculosis, brucellosis and trypanosomiasis. Migrants and mobile populations are also predisposed to sexually transmitted infections (e.g., HIV/AIDS, Syphilis, Gonorrhoea, e.t.c.) given the increased anonymity they enjoy along their routes which further perpetuates transmission in their primary closed communities. Innovative approaches have to be pursued for detection and control of infections among these populations such as leveraging on programs for nomadic populations (nomadic education program in Nigeria), mobile units, One-Health strategy of linking animal health (e.g., manyatta project in Kenya), use of community/village health workers, clinical and public health services. Use of point-of-care tests such as RDTs, lateral flow assays will facilitate prompt diagnosis. Clinical management will be facilitated using more potent antimicrobial agents in shorter regimens, and preferably oral regimens. Approaches such as switch from intravenous to oral therapies as in partial oral endocarditis therapy (POET) and where appropriate promoting surgical therapy rather than long-term medical therapy with follow-up as in Hydatidosis will facilitate care of chronic infections. Mass Drug Administrations (MDA) may be utilized for prevention of certain IDs such as albendazole for soil transmitted helminths, ivermectin for onchocerchiasis and azithromycin for trachoma which has also been shown to improve childhood survival. Overall, health awareness, sensitization and educational programs as well as improving access to care are pivotal for the control of IDs in these populations.